119 A novel kinematic tool to assess upper limb dysfunction in multiple sclerosis. Issue 9 (12th August 2022) - Fernandes, Linford; Coats, Rachel; Mon-Williams, Mark; Ford, Helen
Abstract : Introduction: We assessed upper limb function in people with progressive MS (pwPMS) using a novel kinematic 3D motion capture methodology. Methods: 42 pwPMS and 15 healthy controls reached-and-grasped different objects while movement trajectories were captured with a kinematic assessment system. Clinical measures included the nine hole peg test (9HPT), Expanded Disability Status Scale (EDSS), and patient reported outcomes at baseline and six months. Results: PwPMS had longer reaction and reach times, took longer to pick-up objects and move them between pre-defined positions, and spent more time placing objects, compared to controls. PwPMS had lower peak wrist velocities when reaching for and moving objects. Kinematic assessment demonstrated consistent differences between the mild and severe patients, driven by object grasp dimensions, which weren't captured by 9HPT. There was no correlation between upper limb performance and EDSS, with wide variation in performance across a narrow EDSS range. There was moderate correlation between kinematic assessment and 9HPT. There was no significant change in most of the kinematic or clinical parameters at six months compared to baseline. Conclusions: Our study has created and tested a novel upper limb function assessment tool with better sensitivity and behaviour capture than the EDSS and 9HPT. For the first time, we have captured the spa- tiotemporal patterns of hand function impairment in pwPMS.